Dwa grodziska wczesnośredniowieczne w Zawadzie Lanckorońskiej i Naszacowicach - datowanie metodą archeologiczną i dendrochronologiczną - Krąpiec, Marek; Poleski, Jacek (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1996)
The authors present possibilities and limitations in dating the multi-layer and multi-stage sites with help of the archaeological and dendrochronological methods. As the examples they show two fortified settlements from Małopolska region (Naszacowice and Zawada Lanckorońska)
ill. ; 29 cm
Keywords: early Middle Ages; stratigraphy; dating; dendrochronology; independent determinants of chronology